Energy Saving Opportunities Through Practical Steam System Optimization in Selected Malaysian Industrial Plant of Sabah and Johor - SITTI AISHAH, NAJAMUDIN; Sitti Aishah, Najamudin (Journal of Optimization in Industrial Engineering, 2025)
This thesis explores the optimization of industrial steam systems in selected Malaysian plants in Sabah and Johor to enhance energy efficiency, reduce operational costs, and support national sustainability goals. Malaysia's industrial sector faces challenges such as high energy costs, steam system inefficiencies, and increasing greenhouse gas emissions. Using a mixed-method approach, this study combines on-site measurements (thermal imaging, stack gas analysis) with advanced modelling tools, including the Steam System Assessment Tool (SSAT), 3E Plus Insulation Software, and Solar Heating Industrial Process (SHIP) simulations, to identify and implement significant optimization opportunities. At the Sabah site, targeted measures like feedwater economizers and reduced blowdown rates improved boiler efficiency from 68.6% to 77%, saving 75,276 GJ of energy, 598.3 tons of biomass fuel, and reducing CO₂ emissions by 13,002 metric tons annually. These improvements lowered operational costs by MYR 450,000 per year. At the Johor site, SHIP simulations demonstrated the feasibility of integrating solar thermal technology to enhance feedwater temperatures and boiler efficiency, achieving total cost savings of MYR 362,472.46 through the combination of solar thermal and continuous blowdown heat recovery. This study highlights the importance of steam system optimization in achieving energy savings, economic benefits, and alignment with Malaysia's net-zero carbon targets for 2050. It presents a scalable model for energy-efficient practices across the palm oil and oleochemical industries.